A heuristic evaluation instrument for e–government online software. (4th January 2013) - Hughes, Jerald; Ahluwalia, Punit; Midha, Vishal
An important component of e–government maturity is online software tools for financial analysis directly on the website. This paper develops a novel extension of website heuristic evaluation methodology, contributing a set of guidelines which encompasses not only website content, but also online software quality, based on established software evaluation concerns. Interactive online retirement and tax planning software tools are used as exemplars to demonstrate the evaluation methodology. Online software tools from five nations in four regions of the globe are evaluated for three different kinds of tasks. Results indicate that such tools have considerable room for improvement.